Time to neonatal mortality and its predictors among preterm neonates admitted to the neonatal intensive care unit in northern Ethiopia, 2023/2024: a retrospective cohort study - Brhanu Fisseha; Eskedar Berhanie Gidey; Berhe Gebrehiwot Tewele; Teklehaimanot Gereziher Haile (Archives of Public Health)
Abstract Background A preterm neonate is defined by the World Health Organization as a child delivered before 37 weeks of gestation. In low- and middle-income countries, including Ethiopia, preterm-related complications are serious health problems due to increases in the mortality and morbidity of newborns and children under 5 years of age. The aim of this study was to assess the time to neonatal mortality and its predictors among preterm neonates admitted to the neonatal intensive care unit in northern Ethiopia, 2023/2024. Methods An institution-based retrospective cohort study was conducted among 495 randomly selected preterm neonates in six out of the fourteen general hospitals of Tigray, Ethiopia from October 2023 to June 2024. Epi Data version 4.6 and STATA version 14 were used for data entry and analysis, respectively. Descriptive statistics were carried out to determine the distribution. Kaplan-Meier analysis, life table, and log rank were computed. Cox proportional hazards models were fitted to identify independent predictors of preterm mortality. Results The proportion of preterm neonatal mortality was 109 (22.7%). The overall median survival time was 21 (95% CI: 20, 28) days. Initiation of breast milk (AHR = 0.38 (95% CI: 0.24, 0.61)), respiratory distress syndrome (AHR = 1.9 (95% CI: 1.07,3.63)), perinatal asphyxia (AHR = 2.05 (95% CI: 1.05, 4.00)), receiving kangaroo mother care practice (AHR = 0.5 (95% CI: 0.34, 0.83)), and gestational age (AHR = 1.6 (95% CI 1.07, 2.59) were the predictors of time to death. Conclusion Respiratory distress syndrome, gestational age less than 32 weeks, and perinatal asphyxia at admission were found to be independent risk factors for preterm neonatal mortality. Breastfeeding and receiving kangaroo-mother care were independent preventive predictors of preterm neonatal mortality. It is better to give full emphasis and close follow-up to preterm neonates, especially during the early neonatal period.